Simulation of master-slave optimal synchronous control of double motors based on Simulink. Issue 1 (1st January 2022) - Zhang, Nan; Wu, Shiling; Jia, Yijun; An, Zhaozhe
Abstract: In the working process of vibration machinery, as the output device of power source, the synchronous running state of motor has a decisive influence on the working efficiency of vibration machinery. This paper mainly studies the control synchronization of the double-mass vibration system driven by two motors. Firstly, the dynamic model of the vibration system is established and the vertical displacement equation of the vibration system is derived. Secondly, using adaptive model and PD control algorithm, the controller of motor in vibration system is designed to achieve accurate control of motor and eccentric block motion. Finally, the vibration synchronization effect of the control system and the effectiveness of the control system are verified by modeling and simulation with MATLAB/Simulink software. The test results show that when the main motor is in different initial phases, the variable parameter controller can achieve the control synchronization of the main motor and the slave motor in a short time and achieve a better control synchronization effect. Relevant research results can provide theoretical basis for the design of double-motor vibration machinery.